Nitrosopumilus zosterae sp. nov., an autotrophic ammonia-oxidizing archaeon of phylum Thaumarchaeota isolated from coastal eelgrass sediments of Japan. Issue 8 (18th August 2021) - Nakagawa, Tatsunori; Koji, Mori; Hosoyama, Akira; Yamazoe, Atsushi; Tsuchiya, Yuki; Ueda, Shingo; Takahashi, Reiji; Stahl, David A.
Abstract : A novel mesophilic and aerobic ammonia-oxidizing archaeon of the phylum Thaumarchaeota, strain NM25 T, was isolated from coastal eelgrass zone sediment sampled in Shimoda (Japan). The cells were rod-shaped with an S-layer cell wall. The temperature range for growth was 20–37 °C, with an optimum at 30 °C. The pH range for growth was pH 6.1–7.7, with an optimum at pH 7.1. The salinity range for growth was 5–40 %, with an optimum range of 15–32 %. Cells obtained energy from ammonia oxidation and used bicarbonate as a carbon source. Utilization of urea was not observed for energy generation and growth. Strain NM25 T required a hydrogen peroxide scavenger, such as α-ketoglutarate, pyruvate or catalase, for sustained growth on ammonia. Growth of strain NM25 T was inhibited by addition of low concentrations of some organic compounds and organic mixtures, including complete inhibition by glycerol, peptone and yeast extract. Phylogenetic analysis of four concatenated housekeeping genes (16S rRNA, rpoB, rpsI and atpD ) and concatenated AmoA, AmoB, AmoC amino acid sequences indicated that the isolate is similar to members of the genus Nitrosopumilus . The closest relative is Nitrosopumilus ureiphilus PS0 T with sequence similarities of 99.5 % for the 16S rRNA gene and 97.2 % for the amoA gene. Genome relatedness between strain NM25 T and N. ureiphilus PS0 T was assessed by average nucleotide identity and digital DNA–DNA hybridization, giving results of 85.4 and 40.2 %, respectively. On the basis of phenotypic, genotypic and phylogenetic data, strain NM25 T represents a novel species of the genus Nitrosopumilus, for which the name sp. nov, is proposed. The type strain is NM25 T (=NBRC 111181 T =ATCC TSD-147 T ).